Alessandro Baricco: The Diction of Imagism. (26th July 2021) - Castelli, Alberto
Abstract: The pleasure of a fictional text can be provided by the plot, the characters, and the suspense resulting from their interrelation. In the case of Alessandro Baricco, Italian writer and essayist, the pleasure of reading is given by sounds and images. With the use of unique stylistic elements made of short and nominal sentences, silences, and pauses, Baricco's prose becomes segmented and fragmentary. By binding the motif of his narrative to vague images rather than detailed descriptions, Baricco is shifting the modernist poetics of Imagism to postmodern fiction.